Sikap Mahasiswa Bimbingan dan Konseling Unsyiah dalam Memenuhi Tuntutan Kompetensi Profesional - Kurnia Rezeki; M. Husen; Nurbaity Bustamam (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2020)
ABSTRACT A good attitude in lectures is important to support students in increasing motivation, has a willingness to deepen knowledge, and to develop professional competence to support them to become competent teachers of guidance and counseling and be responsible for the development of students and their profession as teachers or counselors. This study aims to determine the attitude of students in meeting the demands of professional competence described in percentage. The population in this study were FKIP students of the Guidance and Counseling Department totaling 172 students from Leting 2016, 2017, 2018. The sample in this study amounted to 149 students. Sampling in this study using random sampling with the Slovin formula. The method used in this research is a quantitative approach and the type of research is descriptive. Data collection uses a Likert attitude scale. The results showed that the attitudes of students in meeting the demands of professional competence almost half were in the category of "very good" and most of them were in the category of "good", so it can be understood that most students have a positive attitude in meeting the demands of professional competence. The results of the analysis show empirical leaning data curve which shows that the attitude of students in meeting the demands of professional competence in the Guidance and Counseling Department of FKIP is "good", this means that most students have a positive attitude towards the fulfillment of professional competencies both cognitive, affective and propensity to act.Keywords : Attitude in fulfilling professional competence